ANALISIS KINERJA KEUANGAN SYARIAH DALAM PENILAIAN KESEHATAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH JAWA TENGAH (Studi Kasus pada KSPPS Tingkat Jawa Tengah Tahun 2016) - Atika Firda Zahriya; Jaka Isgiyarta (Diponegoro Journal of Accounting, 2019)
This study was aimed analyze the sharia financial performance on health assessment of KSPPS in Central Java in the period of 2016. The analysis based on Deputy Regulation of the Ministry of Cooperatives and Small and Medium Enterprises Republic of Indonesia Number: 07/Per/Dep.6/IV/2016. The samples amounted to 62 KSPPS units in Central Java which were determined by cluster proportionate random sampling technique. The method of data analysis in this study used descriptive statistics. The result of this study indicate that aspects of sharia financial performance are medium. The best aspect of sharia financial performance is the aspect of cooperation identity. While, the worst aspect of sharia financial performance is the aspect of independence and growth.